Analisis hubungan faktor resiko skabies di Pondok Pesantren Darel Hikmah - Erni Setiawati; Zahtamal Zahtamal; Ridwan Manda Putra (SEHATI: Jurnal Kesehatan, 2022)
There are many cases of behavioral and environmental-based diseases, one of which includes those occurring in Darel Hikmah Islamic boarding school. Scabies is a health problem that needs to be addressed, especially in environments with high population density, such as Islamic boarding schools. The purpose of this study was to analyze the relationship between environmental factors, and behavior and to analyze the factors most at risk of scabies at Darel Hikmah Islamic Boarding School. The research was conducted in June-October 2020 at the Darel Hikmah Islamic Boarding School. Based on the results of research that has been done, it is known that the environmental factors associated with the incidence of scabies are lighting and humidity. Behavioral factors related to the incidence of scabies are the habit of washing hands with soap and the habit of changing clothes. The most risk factor for scabies in Islamic boarding schools is humidity. Scabies is a contagious disease caused by an infestation of the Sarcoptes scabiei mite and very often occurs in environments with poor sanitation and unsanitary and healthy living habits. Islamic boarding schools need to take precautions according to their level, namely primary, secondary and tertiary prevention, and regular medical examinations for students.